2018
DOI: 10.1021/acs.langmuir.8b00788
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Investigation of Two-Dimensional DNA Nanoassemblies for Construction of a Nonspecific Sensor Array

Abstract: We have performed a systematic study to analyze the effect of ssDNA length, nucleobase composition, and the type of two-dimensional nanoparticles (2D-nps) on the desorption response of 36 two-dimensional nanoassemblies (2D-NAs) against several proteins. The studies were performed using fluorescently labeled polyA, polyC, and polyT with 23, 18, 12, and 7 nucleotide-long sequences. The results suggest that the ssDNAs with polyC and longer sequences are more resistant to desorption, compared to their counterparts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
28
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 54 publications
2
28
0
Order By: Relevance
“…By altering the surface functionality, the two-element array (dopamine-Fe 3 O 4 NPs and trimethylammonium-Fe 3 O 4 NPs) was able to identify 10 proteins, and differentiate unknown samples with an accuracy of 95%. Nandu et al ( 2018 ) reported a five-element sensor array containing two-dimensional nanoparticles (2D-nps, including MoS 2 , WS 2 , and nGO) and fluorescently labeled ssDNA after a careful screening/filtering process. The displacement of ssDNA from the surface of 2D-nps made the array able to discriminate seven proteins.…”
Section: Multi-element-based Sensor Arrays For Protein Recognitionmentioning
confidence: 99%
“…By altering the surface functionality, the two-element array (dopamine-Fe 3 O 4 NPs and trimethylammonium-Fe 3 O 4 NPs) was able to identify 10 proteins, and differentiate unknown samples with an accuracy of 95%. Nandu et al ( 2018 ) reported a five-element sensor array containing two-dimensional nanoparticles (2D-nps, including MoS 2 , WS 2 , and nGO) and fluorescently labeled ssDNA after a careful screening/filtering process. The displacement of ssDNA from the surface of 2D-nps made the array able to discriminate seven proteins.…”
Section: Multi-element-based Sensor Arrays For Protein Recognitionmentioning
confidence: 99%
“…We have used a single statistical analysis method to identify individual pure target molecules in the past. 8,9,22 Herein, we have adapted a number of ML tools to identify and discriminate complex matrixes reproducibly using four bacterial species.…”
mentioning
confidence: 99%
“…8,9,26 Upon displacement of the fluorescently labeled ssDNAs, the quenched fluorescence recovers. 20,8,9 Each ssDNA interacts differently with each 2Dnp, depending on their nucleobase composition and length, as observed in our previous studies. 9 As a result, the degree of displacement of ssDNAs from each 2D-np surface is observed to be different, creating fingerprint fluorescent patterns.…”
mentioning
confidence: 99%
See 2 more Smart Citations